Topic Working Group on Spatial Analysis and Modeling (TWG-SAM): A report - MacAlister, C.; Notenbaert, An Maria Omer; Pfeifer, Catherine (CGIAR Challenge Program on Water and Food, 2011)
Many modelers and spatial analysts engaged in the Mekong, Ganges, Andes, Volta, Limpopo and Nile basins are grappling with similar issues: How do we get hold of and share quality information? How do we integrate bio-physical and socio-economic data? What are the best methods to fill data gaps and move across scales? How do we select the most appropriate models from the plethora available and transfer these tools and technologies to partners with limited means? How do we link different models and build feed-back loops...? Informal discussions and ad-hoc data exchange have added value to the development of conceptual frameworks and the initial implementation of basin level analyses. In response to this, a Topic Working Group on Spatial Analysis and Modeling (SAM TWG) has been created. The group is currently lead by Charlotte MacAlister, An Notenbaert and Catherine Pfeifer from the Nile Basin. Members from all 6 basins are sharing information, comparing methods, examining and critically appraising each other’s work. The main objective of SAM TWG is to strengthen this community of practice. It facilitates cross- fertilization of approaches thereby strengthening the methodologies applied in the different basins